Screening the Older for Abuse - Sjeničić, Marta (Medicine, Law & Society, 2023)
Many countries are developing instruments to help prevent and recognize violence against the older. In the area of older abuse and its consequences, different screening methods have been developed and adapted to the country in which they are applied. Professionals are often not trained to detect signs of abuse, much less screen for the same, and therefore need continuous training in geriatrics and geriatric medicine. In order to draw attention to the older in the near future, specific measures should be prescribed not only within the framework of current legal regulations and bylaws, but also through guidelines, guides and other professional documents (soft-law), to be taken by state bodies, non-governmental organizations and other actors, for the purpose of screening violence, prevention of violence against the older, treatment of the older who have been subjected to violence and measures against its perpetrators, including forensics in cases of violence against the older. Instruments for organized screening for violence should be introduced in all sectors, but especially in the health and social care sectors, because primary health care and social work centers, in fact, are the gateway to the health and social system and make initial contact with service users, including the older.